Implementasi Pemanfaatan Alokasi Dana Desa (Add) Terhadap Kinerja Perekonomian Daerah Di Indonesia - Yulia Puspitasari Gobel (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
The government has allocated the Alokasi Dana desa (ADD) in the APBD each fiscal year with a large amount. This is for the sake of increasing Indonesia's development specifically to improve regions that can impact on the welfare of society. The purpose of this study was to test the village funding planning for provincial development in Indonesia, the research method used the Sederhaa regression analysis by conducting hypothesis research with the t test. This study uses secondary data consisting of total village funds with economic growth indexes in each province in Indonesia in 2018. The results of this study indicate the fact that Alokasi Dana Desa have a significant effect on regional economic development in Indonesia